Energy performance of buildings in European Union countries and Ukraine - Kariuk, Alla; Mishchenko, Roman; Pents, Volodymyr; Shchepak, Vira (Academic journal Industrial Machine Building Civil Engineering, 2019)
Complex comparative analysis of building energy performance rates in EU countries and Ukraine has been carried out.The relation between building insulation rates and European countries climate condition has been investigated. It is illustratedthat there is a significant gap between building energy efficiency characteristics in Ukraine and in most of the EU countries.Economically justified rates of building envelope heat exchange resistance which can lead Ukraine to common Europeanlevel based on optimized calculations are suggested. The necessity for further increase in building envelope heat exchange resistancerates in order to raise building energy efficiency and put Ukrainian building regulations in harmony with EU countriescorresponding norms is proved.
Keywords: energy performance of buildings; the structure of building energy consumption; building envelope heat exchange resistance; room temperature in winter time